2014
DOI: 10.4102/sajpsychiatry.v20i4.574
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging study of corpus callosum abnormalities in patients with different subtypes of schizophrenia

Abstract: Background. Reductions in the size of the corpus callosum (CC) have been described for schizophrenia patients, but little is known about the possible regional differences in schizophrenia subtypes (paranoid, disorganised, undifferentiated, residual). Methods. We recruited 58 chronically schizophrenic patients with different subtypes, and 31 age-and-gender matched healthy controls. The callosum was extracted from a midsagittal slice from T1 weighted magnetic resonance images, and areas of the total CC, its five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The prefrontal cortex plays an important role in the regulation of complex cognitive, emotional, and behavioural functioning [21]. Thus, prefrontal cortex damage typically results in deficits in judgement, orientation, concentration, and problem-solving ability [21],[22]. Our analysis showed that PCOS women have significantly increased ADC values in anterior cingulate cortex and the dorsomedial and dorsolateral frontal cortexes, suggesting microstructural damages in these areas.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The prefrontal cortex plays an important role in the regulation of complex cognitive, emotional, and behavioural functioning [21]. Thus, prefrontal cortex damage typically results in deficits in judgement, orientation, concentration, and problem-solving ability [21],[22]. Our analysis showed that PCOS women have significantly increased ADC values in anterior cingulate cortex and the dorsomedial and dorsolateral frontal cortexes, suggesting microstructural damages in these areas.…”
Section: Discussionmentioning
confidence: 71%
“…It has been shown that the brain regions involved in mood regulation are the prefrontal cortex (anterior cingulate cortex, dorsolateral frontal cortex, orbitofrontal cortex), subcortical grey matter regions (caudate nucleus and thalamus), and limbic structures (amygdala and hippocampus) [20]. The prefrontal cortex plays an important role in the regulation of complex cognitive, emotional, and behavioural functioning [21]. Thus, prefrontal cortex damage typically results in deficits in judgement, orientation, concentration, and problem-solving ability [21],[22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was manually traced following its edge on the midsagittal slice, where its structure appeared most remarkable. Morphometric measurements were conducted according to the same methods reported previous studies (Hofer and Frahm, 2006;Unlu et al,2014). After drawing the transverse line (AP line) that connects the extreme point of the genu with the extreme point of the splenium in the sagittal plane, a total of 5 areas were measured and evaluated through MRI ( Figure 2).…”
Section: Figurementioning
confidence: 99%